O błędach i ich znaczeniu w rozumowaniach matematycznych - Kolczyńska-Przybycień , Kinga (Studia Edukacyjne, 2022)
In this article we discuss selected types of errors in mathematical thinking. We present their causes, some consequences and the possibilities of using this erroneous reasoning for didactic purposes.